Urban Inequality in the Age of Smart Cities: A Bibliometric Review of Critical Urban Sociology (2014–2024) - Yusuf, Syawal Ghani; Ledyawati; Wijayanti, Ayu; Pakpahan, Fransiskus Novrianto (Business and Investment Review, 2024)
Urban inequality remains a pressing challenge in the 21st century, exacerbated by smart city technologies and neoliberal governance, which often deepen socio-spatial disparities despite their promises of efficiency and sustainability. While qualitative critiques of smart cities exist, few studies employ bibliometric methods to systematically analyze the intellectual structure of urban inequality research, particularly across geographical and institutional contexts. This study addresses this gap by mapping the evolution of critical urban sociology’s engagement with smart city inequality from 2014–2024, using bibliometric analysis of 460 key publications from Scopus and VOSviewer to identify dominant themes, gaps, and emerging debates through bibliographic coupling, co-citation, and keyword co-occurrence analyses. The findings reveal five major clusters, including data-driven governance, digital exclusion, and neoliberal urbanism, with seminal works by Sassen (2014) and Kitchin (2016) dominating the discourse, while also highlighting gaps such as limited Global South perspectives and feminist/postcolonial critiques. Temporal shifts show a growing focus on algorithmic bias and data justice, underscoring the need for inclusive, participatory smart city frameworks. The study concludes by advocating for equitable governance models, democratized technology access, and interdisciplinary approaches to mitigate urban inequality, offering a foundation for future research and policy interventions.